KONTRIBUSI ARISAN ONLINE DALAM MEMENUHI GAYA HIDUP MAHASISWA MENURUT SUDUT PANDANG EKONOMI ISLAM (Studi Kasus Pada Kelompok Arisan Mahasiswa Fakultas Ekonomi Dan Bisnis Islam Universitas Islam Negeri Sumatera Utara) - Adam Alamsyah; Sri Sudiarti; Tri Inda Fadhila Rahma (Universitas Islam Negeri Sumatera Utara, 2021)
The progress of the development of life in Indonesia affects the lifestyle, especially students. Student, someone who demands education at higher education, has many necessities of life to fulfill his studies and daily life. Online arisan is an alternative for students to save money to fulfill their daily needs. This study aims to see how to see members who are online arisan, see which ones contribute to online arisan in fulfilling student lifestyles, and see a review of Islamic economics on online social gathering activities in the Islamic economics faculty of the State Islamic University of North Sumatra. The research method used a qualitative approach with data techniques, namely primary data and secondary data. Research subjects, the owner of the arisan and (9) members of the online arisan. Data techniques are premier data and secondary data. The data analysis methods used in the study were data reduction, data presentation, and conclusion drawing. The results of this study indicate that the lifestyle of students who take part in an online social gathering is classified as hedonistic, the contribution of online arisan to the arisan group is that there are many benefits obtained by members and an Islamic economic review of the online social gathering system is not allowed because it contains elements of usury in it.KONTRIBUSI ARISAN ONLINE DALAM MEMENUHI GAYA HIDUP MAHASISWA MENURUT SUDUT PANDANG EKONOMI ISLAM(Studi Kasus Pada Kelompok Arisan Mahasiswa Fakultas Ekonomi Dan Bisnis Islam Universitas Islam Negeri Sumatera Utara)